EDUKASI PEMANFAATAN LIMBAH BUAH DAN SAYURAN MENJADI ECO ENZYME UNTUK MENDUKUNG PERILAKU RAMAH LINGKUNGAN PADA SISWA SMAN 2 TANJUNG BALAI - Azwana, Azwana; Panggabean, Ellen L.; Lubis , Hilman (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2026)
High school students are the next generation who will protect and safeguard this earth from various damages, both intentional and unintentional. This activity aims to increase students' awareness of environmental conditions in SMAN 2 Tanjungbalai City, North Sumatra, and to practice sustainable organic waste management. This community service activity was carried out by holding training on the use of fruit and vegetable waste as ecoenzymes. The activity was carried out between a team of lecturers from Medan and students of SMAN 2 Tanjung Balai with permission from the school apparatus. This program targets students as agents of change who can utilize fruit and vegetable waste into ecoenzyme solutions that can be used in everyday life, which are safe and environmentally friendly. This activity combines lectures, demonstrations, and practices so that students as participants understand and are able to make ecoenzymes. This activity introduces participants to the concept, benefits, and step-by-step procedures for producing ecoenzymes using organic waste from leftover fruits and vegetables. As a result, students were very happy and gave positive responses because they were able to utilize fruit and vegetable waste in their homes into a multi-purpose solution needed in everyday life. Students, as agents of change, are expected to utilize the knowledge they gain from this activity in their daily lives, thereby reducing waste production. This program emphasizes the importance of empowering high school students as agents of change and the next generation with simple, cost-effective, and impactful innovations.